Longitudinal Trajectories of Quality of Life Among People With Mild-to-Moderate Dementia: A Latent Growth Model Approach With IDEAL Cohort Study Data. (3rd February 2022) - Clare, Linda; Gamble, Laura D; Martyr, Anthony; Sabatini, Serena; Nelis, Sharon M; Quinn, Catherine; Pentecost, Claire; Victor, Christina; Jones, Roy W; Jones, Ian R; Knapp, Martin; Litherland, Rachael; et al.
Abstract: Objectives: We aimed to examine change over time in self-rated quality of life (QoL) in people with mild-to-moderate dementia and identify subgroups with distinct QoL trajectories. Methods: We used data from people with mild-to-moderate dementia followed up at 12 and 24 months in the Improving the experience of Dementia and Enhancing Active Life (IDEAL) cohort study (baseline n = 1, 537). A latent growth model approach examined mean change over time in QoL, assessed with the QoL-AD scale, and investigated associations of baseline demographic, cognitive, and psychological covariates with the intercept and slope of QoL. We employed growth mixture modeling to identify multiple growth trajectories. Results: Overall mean QoL scores were stable and no associations with change over time were observed. Four classes of QoL trajectories were identified: 2 with higher baseline QoL scores, labeled Stable (74.9%) and Declining (7.6%), and 2 with lower baseline QoL scores, labeled Stable Lower (13.7%) and Improving (3.8%). The Declining class had higher baseline levels of depression and loneliness, and lower levels of self-esteem and optimism, than the Stable class. The Stable Lower class was characterized by disadvantage related to social structure, poor physical health, functional disability, and low psychological well-being. The Improving class was similar to the Stable Lower class but had lower cognitive test scores. Discussion: Understanding individual trajectories can contribute to personalized care planning. Efforts to prevent decline in perceived QoL should primarily target psychological well-being. Efforts to improve QoL for those with poorer QoL should additionally address functional impairment, isolation, and disadvantage related to social structure.